Effect of washing on persistence of residues of mancozeb in cardamom (Elettaria cardamomum Maton) capsules - MAICKUTTY P MATHEW, THOMAS BIJU MATHEW, NASEEMA BEEVI, K SUDHARMA, NALINAKUMARI NALINAKUMARI, (Journal of Spices and Aromatic Crops, 1999)
Experiments on degradation of the fungicide mancozeb on cardamom (Elettaria cardamomum) capsules by processing techniques indicated that thorough washing had a profound influence on the removal of surface residues. A waiting period of 8 to 14 days in the case of fresh capsules could be brought down to 3 to 4 days by washing.